Antimicrobial use in a pediatric hospital in Kenya: a point prevalence survey to inform antimicrobial stewardship - Mbuthia, Joseph; Gitonga, Nkatha; Akoth, Winnie; Mutua, Susan; Kusu, Ndinda; Hafner, Tamara; Joshi, Mohan P.; Embrey, Martha (Frontiers in Tropical Diseases, 2025)
IntroductionA baseline point prevalence survey (PPS) was conducted at Gertrude’s Children’s Hospital (GCH), a private pediatric hospital in Kenya, to assess antimicrobial use patterns, adherence to antimicrobial stewardship (AMS) protocols, and compliance with treatment guidelines. The survey aimed to provide insights into antimicrobial prescribing practices in a pediatric setting and address a critical gap in data from private healthcare facilities in Kenya.MethodsThe PPS included all inpatients as of 13 May 2022, excluding those discharged on that date, day cases, and those prescribed topical antimicrobials. Data were collected using a tool adapted from the World Health Organization (WHO) PPS standardized methodology, focusing on antimicrobial prescribing trends, compliance with GCH treatment guidelines, and adherence to WHO’s Access, Watch, and Reserve categorization.ResultsThe results showed that 61% of inpatients were on antimicrobials, with systemic antibacterials (J01) being the most prescribed, particularly third-generation cephalosporins, penicillin combinations, and imidazole derivatives. Ceftriaxone was the most commonly used antimicrobial, and the average number of antimicrobials prescribed per patient was 1.2. Prescribing practices showed a high use of Watch category antibiotics (51%) and a predominant use of the intravenous (IV) route (75%).DiscussionOnly 50% of prescriptions complied with guidelines and microbiological findings; we identified significant areas for improvement, including the need for structured reviews of antimicrobial prescriptions, better alignment with AMS objectives, and enhanced training on treatment guidelines, diagnostic stewardship, and infection prevention and control.ConclusionThe PPS provided valuable data to inform AMS interventions at GCH, the development of policies for IV-to-oral switch criteria, enhancement of the health management system, establishment of antimicrobial ward rounds, and improved education on laboratory result interpretation and appropriate sample collection.